Entering the new normal - psychosocial work environment and health during the transition from full remote to a hybrid work arrangement in a higher education context - Jeffrey Casely-Hayford; Helena Tinnerholm Ljungberg; Emmanuel Aboagye; Christina Björklund; Lydia Kwak; Susanna Toivanen; Gunnar Bergström; Irene Jensen (PLoS ONE, 2026)
This longitudinal study explored the perceptions of psychosocial work factors, work-related health, and job satisfaction of 745 professional service staff, working in a higher education setting in Sweden, during the transition from full remote work to a hybrid work arrangement over 12-months. The study also explored whether these perceptions differed due to gender and household composition. The questionnaire data were analyzed using linear mixed-effects models with estimated marginal means and Bonferroni-adjusted pairwise comparisons. The results showed that while overall perceptions of psychosocial work factors showed modest changes during the transition, except for social support from colleagues, which significantly increased over time. Professional service staff reported higher levels of stress and exhaustion during the transition, while job satisfaction remained unchanged. The results also highlighted significant gender differences during the transition, as women reported less favourable perceptions of psychosocial work factors and higher levels of stress, while men’s perceptions remained largely stable across these outcomes. Significant overall differences in household composition were also observed, as individuals living in single-person households and in single-parent households reported less favourable perceptions of psychosocial work factors and their work-related health compared to cohabitants and cohabitants with children, though all household groups followed similar trajectories during the transition. The findings suggest that higher education institutions should implement action plans for gender equality and family-supportive practices in hybrid work arrangements to ensure that the benefits of hybrid work are accessible to all employees.